Evaluasi Responsif Aktualisasi Pendidikan Soft Skill Terhadap Moralitas Siswa di MI Pare Desa Semoyang - Abdul Manap, Zainul Arifin, Welly Kuswanto (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to responsively evaluate the actualization of soft skill education in relation to students' morality at MI Pare, Semoyang Village. The study is grounded in the need for Islamic elementary schools to ensure that religious habituation, classroom management, and social interaction do not remain formal routines but become meaningful processes for shaping students' moral behavior. A qualitative evaluative approach was employed using Robert E. Stake's responsive evaluation model. Data were collected through school activity observation, semi-structured interviews with teachers and students, documentation of religious habituation, and field notes. The data were analyzed thematically through data reduction, issue coding, a matrix of activities-soft skills-moral behaviors, methodological triangulation, and evaluative conclusion drawing. The findings show that soft skill education is actualized through group discussion, collaborative tasks, classroom duty, the 5S culture, collective prayer, Quran recitation, congregational prayer, teacher modeling, and polite communication. These practices contribute to students' responsibility, discipline, honesty, empathy, social care, and communication ethics. However, several issues remain, including uneven teacher understanding of cross-subject soft skill integration, the influence of digital media on student behavior, and inconsistent family support. The study recommends a practical guide for integrating soft skills, moral reflection after religious activities, stronger teacher role modeling, and collaboration between the madrasah and parents. The article contributes by positioning responsive evaluation as a framework for interpreting soft skill education as a contextual, participatory, and improvement-oriented process of moral formation.